Corn Agroindustry Supply Chain Management in Indonesia: Increasing Added Value and Competitiveness through the Hayami Method - Nur Arifani, Erlina; Mahfudz, Muhammad Syarqim (Universitas Ahmad Dahlan, 2024)
The agro-industry serves as a crucial intermediary for transforming agricultural societies into industrial ones, contributing to a balanced economic structure. This sector processes agricultural products through various methods, adding value and yielding higher profits than raw commodities. Corn, a staple in Indonesian agriculture, is predominantly cultivated with limited post-harvest activities, impeding rural economic growth. This study examines the supply chain management of the corn agro-industry to enhance value addition and competitiveness. Utilizing the Hayami method, the research identifies stages in the corn processing chain, including cleaning, grinding, filtering, and drying, and evaluates the value added at each stage. The analysis reveals that the supply chain involves multiple stakeholders, from farmers to retailers, and highlights the disparity in value addition among different actors. The study concludes that effective supply chain management, risk mitigation, and strategic interventions are vital for sustaining the corn agro-industry. Recommendations include extended mentorship for farmers and the implementation of efficient production practices to ensure long-term sustainability and economic growth.